Vault [videorecording (DVD)] - DeNucci, Tom; DeNucci, Tom; Rossi, Theo, 1975-; Standen, Clive; Johnson, Don, 1950- (Lionsgate, 2019)
Several small-time criminals band together to steal millions of dollars from a vault owned by the mafia in Rhode Island.